2018
DOI: 10.1016/j.nicl.2017.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant brain functional connectivity in newborns with congenital heart disease before cardiac surgery

Abstract: Newborns with congenital heart disease (CHD) requiring open heart surgery are at increased risk for neurodevelopmental disabilities. Recent quantitative MRI studies have reported disrupted growth, microstructure, and metabolism in fetuses and newborns with complex CHD. To date, no study has examined whether functional brain connectivity is altered in this high-risk population after birth, before surgery. Our objective was to compare whole-brain functional connectivity of resting state networks in healthy, term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 58 publications
4
27
5
Order By: Relevance
“…Opposed to our structural connectomics findings, a previous analysis of the functional connectome demonstrated a preserved functional global network architecture in CHD neonates (De Asis-Cruz et al 2018). This contrast in global topological findings could be partly attributed to the exclusion of CHD neonates with parenchymal brain lesions, but could as well arise from temporal differences in functional and structural network maturation.…”
Section: Reduced Integration and Higher Segregation Of Global And Nodcontrasting
confidence: 76%
“…Opposed to our structural connectomics findings, a previous analysis of the functional connectome demonstrated a preserved functional global network architecture in CHD neonates (De Asis-Cruz et al 2018). This contrast in global topological findings could be partly attributed to the exclusion of CHD neonates with parenchymal brain lesions, but could as well arise from temporal differences in functional and structural network maturation.…”
Section: Reduced Integration and Higher Segregation Of Global And Nodcontrasting
confidence: 76%
“…alterations in neural networks are present in neonates with CHD prior to surgery 39 , these data suggest that changes in neural connectivity could be secondary to mutations in the genome rather than solely due to hemodynamic factors, and recent genomic studies have identified candidate genes common to children with CHD and those with NDD, suggesting a genetic basis for CHD-associated NDD 23,24,40,41 . In these subjects, genetic substitutions affect genes involved in chromatin modification, morphogenesis and transcriptional regulation of neuronal tissues as well as in the heart.…”
mentioning
confidence: 90%
“…Non-Central Nervous System (CNS) diseases could also alter brain FC in the newborns. A neonatal congenital heart disease study found that hub or rich-club nodes had reduced FC in full-term newborns with neonatal congenital heart disease when compared to the healthy term controls (De Asis-Cruz et al, 2018). It also indicates that such a pathological attack only targets local hub regions in the subcortical regions and brain stem, as well as the thalamocortical connections.…”
Section: Neurodevelopmental Disorders and Other Diseases Or Hazardousmentioning
confidence: 99%